Glassknapper's Cave, Antler Cave and Wetweather Cave (Scottish Historical and Archaeological Internet Reports, 2005)
This section presents an account of the excavation methodology followed by archaeological description of each of the caves in turn. An important aim of the project was to recover bulk samples from the excavated deposits. Deposits in Glassknapper's Cave were complex and although there was no convincing evidence of substantial structural elements, two stone concentrations appeared to represent artificial arrangements. Three radiocarbon dates ranged from cal AD 770-1160. Antler Cave represented a relative paucity of deposits although it was consistently wet and was not intensively excavated. The cave appears to have been used on a more casual basis than the others. The existence of Wetweather Cave only became apparent during the project. Only a brief assessment was carried out. Occupation appears to date back to the Neolithic and there is evidence for features of some complexity which were cut into the floor of the cave.